2008
DOI: 10.1371/journal.pone.0002903
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Severe Anaemia in Malawian Children

Abstract: BackgroundSevere anaemia is a common, frequently fatal, condition in African children admitted to hospital, but its long term outcome is unknown. Early reports that survivors may be at risk of additional late morbidity and mortality may have significant implications for child survival in Africa. We assessed the short and long term outcome of severe anaemia in Malawian children and identified potential risk factors for death and further severe anaemia.Methodology and FindingsFor 18 months, we followed up childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 22 publications
11
117
1
1
Order By: Relevance
“…Studies have shown that long term survival of children discharged after treatment for malaria, diarrhoea and respiratory infection may be worse than that reported here for children discharged from therapeutic feeding programmes (Islam et al, 1996;Phiri et al, 2008;Roy et al, 1983;Snow et al, 2000;Veirum et al, 2007;West et al, 1999). Indeed, in Bangladesh an incidence mortality rate of 465 deaths per 1000 PY has been reported in children followed in the community after recovery from acute diarrhoea (Islam et al, 1996).…”
Section: Bahwere Et Al 221mentioning
confidence: 50%
“…Studies have shown that long term survival of children discharged after treatment for malaria, diarrhoea and respiratory infection may be worse than that reported here for children discharged from therapeutic feeding programmes (Islam et al, 1996;Phiri et al, 2008;Roy et al, 1983;Snow et al, 2000;Veirum et al, 2007;West et al, 1999). Indeed, in Bangladesh an incidence mortality rate of 465 deaths per 1000 PY has been reported in children followed in the community after recovery from acute diarrhoea (Islam et al, 1996).…”
Section: Bahwere Et Al 221mentioning
confidence: 50%
“…In most cases, it is due to two or more causative agents rather than a single one [1][2][3] . Malaria, bacteraemia, helminthiasis, human parvovirus B19 (B19V) infection and other infections such as tuberculosis and HIV/AIDS have been widely reported as important factors contributing to the high prevalence of anaemia in many populations [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Even though some individual causes have been identified,…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, malnutrition, anaemia, hypoxaemia, longer hospitalization and discharge against medical advice exacerbate this risk. [6][7][8][9][10][11][12] Additional data are needed to guide the development of strategies for effective follow-up care that will reduce post-discharge mortality.…”
Section: Introductionmentioning
confidence: 99%